Sistem Pendukung Keputusan Dalam Pemilihan Perawat Terbaik Menerapkan Metode SAW dengan Pembobotan ROC - Mohammad Aldinugroho Abdullah; Rima Tamara Aldisa (Journal of Computer System and Informatics (JoSYC), 2023)
Activities carried out in the hospital never stop day or night. These activities continue because patients who are sick do not know the term time. Patients will always be there and need help from the hospital both day and night. Therefore, many nurses or nuns are needed to handle complaints from patients every time. A nurse or nurse is someone who has a duty, namely to provide care or care for each individual who is sick. This fact made many people interested in becoming nuns. This resulted in many university graduates graduating with that major. so many apply to become nurses on duty at the hospital. The large number of candidates who applied made it difficult for the hospital to select suitable candidates. Selection that is done manually will take quite a long time and the results of the election are not objective. The solution that can be done to solve these problems is to use a decision support system. Based on the results of this study, information was obtained that a decision support system using the SAW method can solve problems regarding decision making in selecting the best nurse. The result is to produce a value of 0.8160 as an alternative to A4 on behalf of Ratih Setyowati as the best alternative